P081 Effect of bile acid on lymphocyte migration in the small intestine. (25th January 2019) - Shibuya, N; Higashiyama, M; Nishii, S; Mizoguchi, A; Inaba, K; Sugihara, N; Hanawa, Y; Wada, A; Horiuchi, K; Furuhashi, H; Kurihara, C; Hozumi, H; et al.
Abstract: Background: The introduction of the western diet has been proposed as an explanation for the increase in inflammatory bowel disease (IBD) incidence. Among them, greater consumption of fat is known to increase risk of IBD. We have reported that dietary fat augmented intestinal immune system by increasing lymphocyte migration to the intestinal microvessels by using intravital microscope system in the animal models of IBD. High fat diet increases secondary bile acid, especially deoxycholate (DCA), which is reported to be involved in the exacerbation of IBD along with direct effect of fat. Each bile acid distinctively affects gut immunity and its mechanism remains to be clarified. Recently, aberrant migration of lymphocytes to intestinal mucosa has been regarded one of critical pathogenesis of IBD. We aimed to investigate the effect of several kinds of bile acid on gut immunity in the view point of intestinal microcirculation. Methods: (1) Effect of bile acid exposure on intestinal mucosa: Thoracic duct lymphocytes (TDL) were collected from the thoracic duct of donor rats. We intravenously injected CFSE-fluorescence labelled TDL into recipient rats, and migration in intestinal mucosa was observed by a confocal microscope to evaluate the TDL migration. In some recipient rats, bile acids were injected into ligated ileum at both ends to evaluate the direct effect on intestinal mucosa. Tauro Colic Acid Natrium (tauro-CANa, 4 mM) or DCA (4 mM), PBS were injected into the intestinal lumen. PBS was used as a control sample. Mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) neutralising antibody was administered intravenously in some rats. Mucosal damages were measured histologically. (2) Effect of bile acid exposure on TDL: TDL were cultured at 4°C for 2 h with above-mentioned bile acids. Expression levels of L-selectin and α4 integrin in the obtained lymphocytes were examined by flowcytometry. Results: (1) A small number of lymphocytes adhered to intestinal microvessels in control group. There was no change in TDL adhesion in the Tauro-CANa exposed group. TDL adhesion increased in the DCA exposed group. Increased lymphocyte adhesion by DCA was partially blocked by neutralising antibody of MAdCAM-1. Histologically, a part of intestinal mucosa was damaged by DCA, and inflammatory cell infiltration was observed in the mucosa. (2) Expressions of α4 integrin and L-selectin on TDL did not alter with or without addition of bile acids. Conclusions: DCA caused injury of ileal mucosal epithelium and increased lymphocyte adhesion to the vascular endothelium in the ileal mucosa, suggesting that the gastrointestinal immunity could be altered by some bile acids via increase in expression of adhesion molecules on microvessels.